1991
DOI: 10.1002/elps.1150120615
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the electrophoretic mobility of OmpC due to variations in the ammonium persulfate concentration in sodium dodecyl sulfate‐polyacrylamide gel electrophoresis

Abstract: Studies on Salmonella typhi and Salmonella typhimurium outer membrane proteins have shown that the relative position of OmpC porin in sodium dodecyl sulfate.polyacrylamide gel electrophoresis undergoes an important shift when the concentration of ammonium persulfate in the running gel is increased from 6 to 12 mM. The apparent molecular mass at these concentrations was estimated to be 34 and 40 kDa, respectively. Under similar electrophoretic conditions the apparent molecular mass estimated for OmpF was 37.6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…To measure the relative abundance of OmpD in the serovar Typhimurium outer membrane, we prepared outer membrane fractions from cells grown at 37°C in Luria-Bertani (LB) medium as described by Schnaitman (24) and modified by Lobos and Mora (11), resolved the proteins in these fractions by sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis in 12.5% slab gels, and revealed these proteins by staining with Coomassie blue. Figure 1 shows that when wild-type strain LT2 is grown aerobically in LB medium at 37°C, it produces four abundant porins, OmpC, OmpF, OmpD, and OmpA, among which OmpD is the most abundant.…”
mentioning
confidence: 99%
“…To measure the relative abundance of OmpD in the serovar Typhimurium outer membrane, we prepared outer membrane fractions from cells grown at 37°C in Luria-Bertani (LB) medium as described by Schnaitman (24) and modified by Lobos and Mora (11), resolved the proteins in these fractions by sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis in 12.5% slab gels, and revealed these proteins by staining with Coomassie blue. Figure 1 shows that when wild-type strain LT2 is grown aerobically in LB medium at 37°C, it produces four abundant porins, OmpC, OmpF, OmpD, and OmpA, among which OmpD is the most abundant.…”
mentioning
confidence: 99%
“…Previously, we have shown that the protein with an apparent molecular mass of 36 kDa corresponds to the porin OmpC (12,44). Bands corresponding to the other induced proteins were isolated, and the N-terminal sequences of the proteins present in these bands were determined by sequential Edman degradation and are the sequences of serovar Typhi FliC (flagellin) and the MalL, PhoE, and Tsx porins ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Outer membrane fractions were prepared as described by Lobos and Mora (44) based on a modification of the method of Schnaitman (62), and proteins in these fractions were separated in 12.5% polyacrylamide gels. Bacteria were grown to the mid-exponential phase (optical density at 600 nm [OD 600 ], 0.2), chilled on ice, pelleted by centrifugation at 3,000 ϫ g for 15 min at 4°C, resuspended in lysis buffer (10 mM Tris-HCl, pH 8, 10 mM MgCl 2 ), and sonicated, and the preparations were supplemented with 2 mM phenylmethylsulfonyl fluoride.…”
mentioning
confidence: 99%
“…Subcellular fractionation was performed by a modification of a method previously described (Lobos & Mora, 1991). Briefly, bacteria were cultured in LB pH 7.0 400 mM NaCl to exponential phase without aeration.…”
Section: Methodsmentioning
confidence: 99%